IMPROVING ENGLISH LANGUAGE PROFICIENCY THROUGH ENGLISH WEEKEND PROGRAMME AT MAA AN ACTIVITY-BASED: English Weekend - Utari, Gita; Andriyani, Zulfi Zumala Dwi (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
This study aims to determine the improvement of English language skills of students of Madrasah Aliyah Al-Amiriyyah (MAA) through the English Weekend program, with a qualitative approach and case study design. The Object of the study consisted of 200 MAA students participating in the English weekend program, as well as 9 tutors from KH. Mukhtar Syafaat University. Data collection was carried out through three main techniques: semi-structured interviews with the Head of Activity Coordinators, Prajapka, and 2 tutors, direct observation of learning activities, and collection of documentation related to the program, including learning modules and student progress notes. Data analysis was carried out using a thematic analysis approach, which included identifying main themes such as improving speaking skills, increasing vocabulary and student confidence, and student motivation to learn English. To ensure the validity and reliability of the study, data triangulation was carried out by comparing information from various sources and discussing the findings with colleagues. This study explores the improvement of English language skills of students of Madrasah Aliyah Al-Amiriyyah (MAA) through the English Weekend program which adopts an activity-based approach. In an increasingly connected world, English language skills are essential.